KEPEMIMPINAN DAN KORUPSI (SIMBIOSIS MUTUALISME) - Hidayanto, M. Fajar (Islamic University of Indonesia, 2005)
The leadership and corruption in this era denote twoi sides of a coin and closed related to each other. The corruption happe s in Indonesia because of untrusted leadership. The standard that can be an indicator of successful leadership is not enough only to free and does not punish corruptors. The long term and ideal leadership is clean and free from corruption. Kata kunci: pemimpin, korupsi, curang, dan negara